Developing English – Indonesia Pictorial Vocabulary Mini Dictionary for Hearing Impaired Students - Putera, Alam Aji; Paraswati, Hazlinda; Kamila, Elva Laela; Putri Nabila, Diva Amilta (Institut Agama ISlam Negeri Palangka Raya, 2023)
This research aims to develop an Indonesian English dictionary for hearing-impaired students at Special School of Linguistics (SLB) Idayu Malang 2. The research titled